Introduction to aircraft aeroelasticity and loads - Wright, Jan R. (Aerospace series (Chichester, England), 2007)
Aircraft performance is influenced significantly both by aeroelastic phenomena, arising from the interaction of elastic, inertial and aerodynamic forces, and by load variations resulting from flight and ground manoeuvres and gust / turbulence encounters. There is a strong link between aeroelasticity and loads, and these topics have become increasingly integrated in recent years. Introduction to Aircraft Aeroelasticity and Loads introduces the reader to the main principles involved in a wide range of aeroelasticity and loads topics. Divided into three sections, the book begins by revi.